2009
DOI: 10.1080/07347330802616084
|View full text |Cite
|
Sign up to set email alerts
|

Amazon Heart: An Exploration of the Role of Challenge Events in Personal Growth After Breast Cancer

Abstract: High-profile events where in response to the experience of breast cancer women take on adventure activities to raise awareness and/or funds for breast cancer are increasing. These activities offer physical and psychological challenges within a peer support group setting. We investigated the experiences of 21 breast cancer survivors who participated in a 7-day breast cancer awareness motorcycle ride. Assessments included a qualitative pre/postinterview, solicited diary, pre-6-month follow-up survey. Measures in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 25 publications
2
41
1
1
Order By: Relevance
“…Further, our results are consistent with qualitative studies showing that benefit finding is associated with receiving positive social support from peers (Dunn et al, 2009), implying a mediating effect of benefiting finding -adjustment relationships.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Further, our results are consistent with qualitative studies showing that benefit finding is associated with receiving positive social support from peers (Dunn et al, 2009), implying a mediating effect of benefiting finding -adjustment relationships.…”
Section: Discussionsupporting
confidence: 81%
“…given that one of the perceived gains associated with benefit finding is improved social relationships, this pathway is highly plausible (Dunn et al, 2009). To our knowledge this is the first study to test these associations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ride elicits strong emotions, anxiety and fear for participants as they face these new experiences and overcome the physical challenges [20]. This event can also provide a catalyst for PTG [20,21]. An initial qualitative study showed prominent themes reported by participants to include identifying with other cancer survivors and close connections with the women and the whole group [21].…”
Section: Introductionmentioning
confidence: 94%
“…As a consequence, survivors may devote much time and effort to strengthening and developing confidence in their bodies again, to the point of establishing new physical identities as capable athletes (e.g., Dunn, Campbell, Penn, Dwyer, & Chambers, 2009;Parry, 2008;Sabiston, McDonough, & Crocker, 2007).…”
Section: Emotional Processing In Cancer Survivorsmentioning
confidence: 99%